2009
DOI: 10.1007/s11033-009-9551-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of liver Wap65 cDNA in ayu (Plecoglossus altivelis) and mRNA expression changes following Listonella anguillarum infection

Abstract: The teleost warm temperature acclimation related 65 kDa protein (Wap65) is a plasma glycoprotein with the potential roles in heat adaptation, heme recycling, immune response and copper metabolism. It is most homologous to the mammalian hemopexin, which is the plasma transporter of heme. A full-length cDNA clone of the Wap65 gene, 1,534 bp in size, was isolated from the fish ayu (Plecoglossus altivelis). Its deduced amino acid sequence of 439 residues had 60.4-65.4% and 38.3-47.3% identical to fish Wap65-2-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 22 publications
4
21
0
1
Order By: Relevance
“…Overall, the transcriptional responses of mud loach Wap65 genes during bacterial and LPS challenges were largely isoform-specific-the mud loach Wapa65-2 isoform was preferentially activated in most cases regardless of tissue type. This modulation pattern is in accordance with previous studies of other fish species, including catfish (I. punctatus) (Sha et al, 2008), ayu (Plecoglossus altivelis) (Shi et al, 2010) and rockbream (O. fasciatus) (Lee et al, 2014). A similar phenomenon (i.e., Wap65-2-exclusive or preferential activation in response to LPS or bacterial challenge) was also reported in the liver of the mud loach in our previous work, although Wap65-1 was downregulated only slightly during challenges in the intestine, kidney and spleen examined in the present study (Cho et al, 2012).…”
Section: Further Comparison Of Tf-binding Motifs In Mud Loachsupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, the transcriptional responses of mud loach Wap65 genes during bacterial and LPS challenges were largely isoform-specific-the mud loach Wapa65-2 isoform was preferentially activated in most cases regardless of tissue type. This modulation pattern is in accordance with previous studies of other fish species, including catfish (I. punctatus) (Sha et al, 2008), ayu (Plecoglossus altivelis) (Shi et al, 2010) and rockbream (O. fasciatus) (Lee et al, 2014). A similar phenomenon (i.e., Wap65-2-exclusive or preferential activation in response to LPS or bacterial challenge) was also reported in the liver of the mud loach in our previous work, although Wap65-1 was downregulated only slightly during challenges in the intestine, kidney and spleen examined in the present study (Cho et al, 2012).…”
Section: Further Comparison Of Tf-binding Motifs In Mud Loachsupporting
confidence: 93%
“…Besides its essential function in thermal acclimation, this serum glycoprotein is also involved in various other cellular pathways, especially those relating to innate immunity (Sha et al, 2008). The potential role of WAP65 proteins as an immune modulator has been demonstrated in several previous studies on dynamic modulations in fish tissues during immune-stimulating challenges and/or environmental perturbation treatments (Aliza et al, 2008;Sha et al, 2008;Shi et al, 2010). Teleosts typically possess two functional WAP65 isoforms (WAP65-1 and WAP65-2) and previous reports have suggested that these two isoforms have been functionally diversified or subfunctionalized, where the fish WAP65-2 isoform generally has a closer orthology to human hemopexin (HPX) than WAP65-1 (Cho et al, 2012;Lee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…15) In the seabass, higher expression of Wap65-2 transcripts in the liver was found after nodavirus infection, whereas no significant differential expression was detected in the liver for Wap65-1. 14) As for mRNA expression following the infection of various tissues, Wap65-2 transcripts were found to be expressed in the medaka liver, 22) the ayu liver, 5) and the mud loach liver, 15) and were upregulated by bacterial infection. C (4) for 1 h prior to cell harvest.…”
Section: Temperature-stimulated Gene Expressionmentioning
confidence: 99%
“…1,2) The physiological responses of fish to seasonal temperature changes, spanning weeks to months and distinguished from short-term adjustment, in which heat-shock proteins are involved, are now being studied at both the cellular and the molecular level. [3][4][5] Among the physiological responses to warm temperatures, the synthesis of warm-temperature acclimation-associated protein Wap65 has been clearly demonstrated.…”
mentioning
confidence: 99%
“…因其与暖温适应相关且相对分子质量为 6.5×10 4 而 得名。 该类蛋白存在 Wap65-1 和 Wap65-2 两种异构 体 (Hirayama et al, 2003)。研究表明, Wap65-2 具有 多种生物学功能, 它与鱼类暖温适应 (Hirayama et al, 2003)、重金属胁迫 (Aliza et al, 2008)和生长发育 (Hirayama et al, 2004) 等 紧 密 相 关 。 近 年 来 , Wap65-2 在细菌感染性免疫应激中的作用日益引起 人们的关注 (Cho et al, 2012;Li et al, 2011;Peatman et al, 2008;Sha et al, 2008;Shi et al, 2010)。目前, 多种鱼类 Wap65-2 基因序列已被克隆, 包括东方红 鳍鲀(Takifugu rubripes) (Hirayama et al, 2003)、青鳉 (Oryzias latipes) (Hirayama et al, 2004) 、 蓝 鲇 (Ictalurus furcatus) (Peatman et al, 2008)、斑点叉尾 鮰 (I. punctatus) (Sha et al, 2008) 、 剑 尾 鱼 (Xiphophorus hellerii) (Aliza et al, 2008)、真裸南极 鱼(Harpagifer antarcticus) (Clak & Burns, 2008)、香 鱼(Plecoglossus altivelis) (Shi et al, 2010)、欧洲海鲈 (Dicentrarchus labrax) (Sarropoulou et al, 2010)和大 鳞泥鳅(Misgurnus mizolepis) (Cho et al, 2012 (Li et al, 2009)…”
unclassified